Within the Whole Body: An Interview with Ishmael Hope and Will Geiger on Tlingit House Screens and Indigenous Phenomenology. Issue 1 (1st June 2019) - Neely, Sol; Hope, Ishmael; Geiger, Will
Abstract : On a cold, snowy January night in Juneau, Alaska, Will Geiger and I convened at Ishmael Hope's home—with his wife, Lily, and their five children—for dinner and cordiality in advance of our recording session. The Hope family is exceedingly generous with their time and knowledge, and, as is the case whenever we gather at the Hope home, one can palpably discern the multigenerational inspirations and relations that sustain their work, artistry, and community involvement. Once the children went to bed, we dimmed the lights and pulled out our books. When the editors of Screen Bodies told me that the journal was interested in expanding notions of screen beyond cinema, I inquired about the possibility of interviewing Ishmael Hope and others on Tlingit house screens and, by a kind of phenomenological appeal, of focusing the conversation through a concern for embodiment. Originally, Ishmael and I invited Will Geiger and Forest Haven, a brilliant Tsimshian PhD candidate from University of California, Irvine, to participate, but Forest was unfortunately unable to attend. Over the years, I have worked closely with these three on a number of academic projects, developing a tight and trusted friendship sustained by mutual respect and interwoven eruditions.